2012
DOI: 10.14238/pi52.4.2012.229-32
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exclusive breastfeeding on reducing acute respiratory infections in low birth weight infants

Abstract: Background Infants who are breastfed receive natural protection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…[ 16 ] Tallo et al also found that LBW infants who were exclusively breast fed till 4 months of age had lower risk of morbidities than those who were not exclusively breast fed. [ 17 ] Oddy et al and Lamberti et al also had similar findings in their studies. [ 18 19 ]…”
Section: Discussionsupporting
confidence: 64%
“…[ 16 ] Tallo et al also found that LBW infants who were exclusively breast fed till 4 months of age had lower risk of morbidities than those who were not exclusively breast fed. [ 17 ] Oddy et al and Lamberti et al also had similar findings in their studies. [ 18 19 ]…”
Section: Discussionsupporting
confidence: 64%
“…Tallo et al and Lamberti et al found similar findings in their studies. 24,25 A study conducted in South India by Kattula et al shown that, acute respiratory infection and other morbidities risk is lower in exclusively breastfed infants. 26 Singh et al showed that, the commonest morbidity was diarrhea (49.09%) followed by ARI (32.73%).…”
Section: Developmental Milestonesmentioning
confidence: 99%